Physiotherapy utilisation by sports physicians for musculoskeletal injuries in selected elite sports in Nigeria - U. Ushotanefe; F. E. Mbajiogu; A. O. Sanya (AOSIS, 2000)
In Nigeria, the majority of injured athletes seen in sports physiotherapy units are referred by sports physicians. The extent to which a physician utilises the services of physiotherapy in sport depends largely on the level of awareness or knowledge of physiotherapy services that such physicians have. This survey evaluated the degree of utilisation of physiotherapy services for the treatment of injuries during preparation for multi-sports events by sports physicians in selected elite sporting events in Nigeria. One hundred and twenty-eight athletes, coaches, sports administrators, scientists, medical doctors and physiotherapists located at four different camping sites, were sampled. The responses between different professional groups on the non-utilisation of physiotherapy services by sports physicians during preparation for multi-sport events, was not significant. However, Nigerian professionals who were surveyed, accepted the hypothesis that sports physicians did not utilize physiotherapy services for the management of musculoskeletal injuries during training and pre-games preparation in selected elite sports in Nigeria. This retrospective study of the actual referral records at the clinic of the sports medicine centre revealed that 20 (91%) different types of musculoskeletal injuries sustained by volley ball players were referred for physiotherapy. Nine (56.3%) injuries sustained by basketball players, 62 (87.3%) by track and field athletes, and 6 (74%) by football players were referred for physiotherapy between 1992 and 1995. The majority of the injuries sustained were ligamentous sprain and muscular strain with joints of the lower limbs and the back mostly affected.